2020
DOI: 10.3390/s20205876
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Biofeedback Improves Human-Robot Compliance during Ankle-Foot Exoskeleton-Assisted Gait Training: A Pre-Post Controlled Study in Healthy Participants

Abstract: The adjunctive use of biofeedback systems with exoskeletons may accelerate post-stroke gait rehabilitation. Wearable patient-oriented human-robot interaction-based biofeedback is proposed to improve patient-exoskeleton compliance regarding the interaction torque’s direction (joint motion strategy) and magnitude (user participation strategy) through auditory and vibrotactile cues during assisted gait training, respectively. Parallel physiotherapist-oriented strategies are also proposed such that physiotherapist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…We found that the instruction given to participants during exosuit-applied plantarflexion resistance training also played an important role in targeting the plantarflexors. Although providing no explicit instructions enabled us to capture the natural tradeoff between intralimb and interlimb changes in kinetics, the importance of task-specific instructions is well recognized both in the exoskeleton [ 65 ] and rehabilitation fields [ 66 , 67 ]. In the two-subject exploratory study, participants generated sufficient biological ankle torque to match or overcome the applied torque when instructed to pushoff against the exosuit-applied resistance, while only partially offsetting the applied torque when uninstructed.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the instruction given to participants during exosuit-applied plantarflexion resistance training also played an important role in targeting the plantarflexors. Although providing no explicit instructions enabled us to capture the natural tradeoff between intralimb and interlimb changes in kinetics, the importance of task-specific instructions is well recognized both in the exoskeleton [ 65 ] and rehabilitation fields [ 66 , 67 ]. In the two-subject exploratory study, participants generated sufficient biological ankle torque to match or overcome the applied torque when instructed to pushoff against the exosuit-applied resistance, while only partially offsetting the applied torque when uninstructed.…”
Section: Discussionmentioning
confidence: 99%
“…Electric actuators were the most popular actuators deployed in the reviewed PAEs. They were powered by on-board battery packs [37,41,56,57,61,[65][66][67][76][77][78][79][80][81][82][83][84]86,87,94,[100][101][102]112,113,115,[118][119][120]126,127,130,144,145,[156][157][158][159][160][172][173][174][175]177,184,187,189,234,235], DC off-board power supply units [10,…”
Section: Low-level Control and Machine-machine Sensorsmentioning
confidence: 99%
“…Encoder[38,40,42,58,62-64,68,69,72,73,85,86,100,103,104,106,108- 110,117,118,138,139,142,149-151,159- 162,165,173,178,181,185-188,202,206,207,210],Potentiometer[10,43,59,101,102,114,143,147,148,154,155,166,167,170,171] …”
mentioning
confidence: 99%
“…The ankle joint is one of the important joints of the human body. The survey shows that ankle joint injuries account for 7% to 10% of the total number of patients admitted to the emergency department every day [1][2][3][4]. Ankle fracture patients are more common clinically, and the incidence accounts for 4% to 5% of systemic fracture injuries [5][6].For the elderly, as the age increases, the flexibility of the limbs gradually decreases, and severe patients may have foot circulation disorders [7][8][9].Ankle sprains are also a common sports injury.…”
Section: Related Workmentioning
confidence: 99%